2000
DOI: 10.1074/jbc.275.2.1095
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Develops a Specific Form of Small Heat Shock Protein Complex Composed of MKBP/HSPB2 and HSPB3 during Myogenic Differentiation

Abstract: Previously, we identified a new mammalian sHSP, MKBP, as a myotonic dystrophy protein kinase-binding protein, and suggested its important role in muscle maintenance (Suzuki, A., Sugiyama, Y., Hayashi, Y., Nyu-i, N., Yoshida, M., Nonaka, I., Ishiura, S., Arahata, K., and Ohno, S. (1998) J. Cell Biol. 140, 1113-1124). In this paper, we develop the former work by performing extensive characterization of five of the six sHSPs so far identified, that is, HSP27, ␣B-crystallin, p20, MKBP/ HSPB2, and HSPB3, omitting l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
261
1
10

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(289 citation statements)
references
References 51 publications
17
261
1
10
Order By: Relevance
“…In the present study, the expression of MgTCTP mRNA was dominantly detected in muscle, which was different from previous report on Venerupis philippinarum TCTP [11]. It was suggested that MgTCTP perhaps played an important role in muscle maintenance of M. galloprovincialis, as this tissue was frequently affected by heat, oxidative and mechanical stress [31]. Additionally, the high expression level of MgHSPA12A and MgTCTP in gonad perhaps indicated an essential role in reproductive processes, which was in agreement with Kappé et al, who found that some sHSPs were specially expressed in human testis [32].…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, the expression of MgTCTP mRNA was dominantly detected in muscle, which was different from previous report on Venerupis philippinarum TCTP [11]. It was suggested that MgTCTP perhaps played an important role in muscle maintenance of M. galloprovincialis, as this tissue was frequently affected by heat, oxidative and mechanical stress [31]. Additionally, the high expression level of MgHSPA12A and MgTCTP in gonad perhaps indicated an essential role in reproductive processes, which was in agreement with Kappé et al, who found that some sHSPs were specially expressed in human testis [32].…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, as a result of their ubiquitous role in interacting with and stabilising a wide range of partially unfolded proteins against aggregation, sHsps are involved in many processes central to disease development and manifestation. These include cellular growth and differentiation [84,162,163]; interaction with cytoskeletal components such as actin and intermediate filaments [70,164,165]; and apoptosis [166]. Several of the sHsp family members (Hsp27, HSPB2, Hsp27, Hsp20 and Bc) have been attributed a protective role in the development of neurodegenerative and neuromuscular diseases, roles thought to be related to their abilities to both stabilise target proteins and to interact with cytoskeletal elements as the key features of these diseases are protein aggregation and defective axonal transport [70].…”
Section: Section Iii: Shsps and Their Roles In Diseasementioning
confidence: 99%
“…To-date, there is also evidence for the formation of hetero-oligomeric complexes between αA-and αBc [37,54], αAc and Hsp27 [81], HspB2 and HspB3 [84,85], αBc and Hsp20 [86] and Hsp27 and Hsp20 [82]. However, caution is required in interpreting work that has involved adding a bulky tag directly to the sHsps to measure sub-unit exchange (e.g.…”
mentioning
confidence: 99%
“…maintaining myofibrillar integrity [25] HSPB4 (aAcrystallin) brain: not reported low in: sciatic nerve [2] none none n.a.…”
Section: Introductionmentioning
confidence: 99%
“…activation of DMPK [24]; maintaining myofibrillar integrity [25] HSPB3 (HSPL27) low in: cortex, cerebellum, spinal cord, sciatic nerve (RT qPCR) [1][2][3] high [4] high [4] n.a.…”
Section: Introductionmentioning
confidence: 99%